Las Senso-Percepciones en diferentes situaciones de Aprendizaje en los niños de 3 a 4 años de la Unidad Educativa Fernando Daquilema, de la Parroquia Maldonado, Cantón Riobamba Provincia de Chimborazo, en el año lectivo 2014 – 2015 - Samaniego Sani, Vivia Marcela (2016)
The topic called "The sense-perceptions in different learning situations in children 3 to 4 years of Fernando Daquilema Education Unit of the Maldonado parish, canton Riobamba Chimborazo province, in the school year 2014 2015" .The performed with in order to analyze the importance of the development of the senses in the learning process, one auditory Perceptual skills, success depends on perception, discrimination and auditory memory that is acquired in childhood and internal influences, their deficiency will cause confusion, additions in the process of reading and writing., for such reasons specific objectives were geared towards the development of Perceptual skills. It was designed not as experimental, given that departed from an observational diagnosis to know the current reality of students, then planted activities applied and verify the respective scopes v. The research is descriptico - explanatory, describing give the necessary explanations of why they are learning or not children, this was accompanied with the theoretical framework related to the two study variables, such as Perceptual skills to break new learning situations. Subsequently the analysis and interpretation of the information collected with the instrument of data collection used throughout the research is presented, as were the observation as a technique and observation sheet within the achievements of this research process is the confidence and security that showed children to perform different activities memory, discrimination and auditory perception, the use of musical instruments were creative and striking, besides the use of images allowed the development of language and discrimination of syllables, it indicate that the game was the transverse axis in its realization, is with each activity new learning situations begins, therefore the activities proposed in the guide are motivations for new forms or learning situations recommending implementation and enforcement .